AGAMA DAN POLITIK: Studi Pemikiran Soekarno tentang Relasi Agama dan Negara - Muhammad Soleh Aminullah (Jurnal Sosiologi Agama, 2020)
This paper examines the basic state relating to religion and the state. Which of these reforms emerged as a different response between Islamic nationalist groups and secular nationalist groups. Islamic nationalist groups ask for a state based on religion. While secular functionalist groups believe that in the basic formulation of the state, religion must be separated from the state. The first opinion (Islamic nationalists) is based that the majority of Indonesia’s population is Muslim, and conversely the second group holds that Indonesia is a plural state consisting of various groups by wanting Pancasila as the basis of the state. This paper uses descriptive literature study method, meaning that materials are collected from various literatures in order to collect data relating to religious and state relations according to Sukarno. So that it can be understood that the separation of religion and state in Sukarno’s view there are at least three main points. Besides that, Sukarno’s thoughts were also inspired by Kemal Attatur from Turkey and Ali Abdurraziq and other reformers. The separation of religion and state is done for the sake of national unity, bearing in mind that the Indonesian nation is a plural nation. The separation of religion and state in question will not rule out the teachings of Islam, and the building of nationalism in question is not chauvinism, but nationalism which makes Indonesian people become servants of God who live in the spirit and soul of religion.